2011
DOI: 10.2174/138945011794815356
|View full text |Cite
|
Sign up to set email alerts
|

The Targets of Curcumin

Abstract: Curcumin (diferuloylmethane), an orange-yellow component of turmeric or curry powder, is a polyphenol natural product isolated from the rhizome of the plant Curcuma longa. For centuries, curcumin has been used in some medicinal preparation or used as a food-coloring agent. In recent years, extensive in vitro and in vivo studies suggested curcumin has anticancer, antiviral, antiarthritic, anti-amyloid, antioxidant, and anti-inflammatory properties. The underlying mechanisms of these effects are diverse and appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
412
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(452 citation statements)
references
References 234 publications
9
412
0
11
Order By: Relevance
“…However, curcumin and quercetin exhibited significant hepetoprotection in experimental setups as reported previously Chirumbolo, 2010;Lekic et al, 2013;Zhao et al, 2011;Zhou et al, 2011 (Gupta, 1994).…”
Section: Scientific Rationale For the Traditional Use Of Some Plants supporting
confidence: 82%
“…However, curcumin and quercetin exhibited significant hepetoprotection in experimental setups as reported previously Chirumbolo, 2010;Lekic et al, 2013;Zhao et al, 2011;Zhou et al, 2011 (Gupta, 1994).…”
Section: Scientific Rationale For the Traditional Use Of Some Plants supporting
confidence: 82%
“…In a recent meta-analysis on clinical trials it was concluded that curcumin lowers CRP levels (Sahebkar, 2014). It can also lower IL-6 (Belcaro et al, 2010, Zhou et al, 2011 and TNF-Į levels (Aggarwal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[4] Curcumin has been widely used in Eastern populations, particularly as a traditional medicine in India and China, for the treatment of many diseases, including hepato-biliary, skin, rheumatoid, and gastrointestinal system diseases. [5] The protective features of curcumin, first and foremost its antioxidant and anti-inflammatory effects, have been shown in clinical and experimental studies.…”
Section: Introductionmentioning
confidence: 99%